Saint Vincent and the Grenadines. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2021 are identified, with respect to the needs and interests of the country, strengthening in matters of soil and water management, fertilizers, composting, climate change, seedling production, fodder, food quality, financing, vegetable production, for which 149 kg of vegetable seeds were supplied. Likewise, post-COVID-19 care services and care for the recovery from the eruptions caused by the La Soufriere Volcano were provided. Finally, work was done on a digital application for agricultural extension and on a website; as well as in the support of MSME producers and in the validation of damages in the forestry, fishing and agriculture sectors.